Modelagem estatística para a estimativa mensal de horas e unidades de frio em regiões de planalto do Rio Grande do Sul e Santa Catarina - Boligon Minuzzi, Rosandro (Revista Ceres, 2025)
The objective of this study was to obtain and evaluate models for the monthly estimation of chilling hours/units based on air temperature data in the Plateau regions of Rio Grande do Sul and Santa Catarina. Data of air temperature were used from May to August 2012 to 2017 of seven meteorological stations. For each month, the chilling hours/unit were calculated by the Utah method and the sum of temperatures lower or equal to 7.2 °C that were correlated with the minimum and average monthly temperature by the regression analysis. Six statistical methods were used to evaluate the monthly estimate of chilling hours/units obtained by previously obtained models. The minimum temperature and the monthly average explained between 65 and 96% of the chilling hours by the temperature threshold d” 7.2 °C and the chilling units by the Utah method. The minimum temperature and the monthly air average are recommended for the estimation of chilling hours and chilling units, respectively. The climatic variability of the winter in the study region results in different performances of the models of estimates of chilling hours/units.